Sistem Informasi Pengawasan Internal Inspektorat Berbasis Client Server - Dilson Dilson; Lilik Suhery (Elkawnie: Journal of Islamic Science and Technology, 2016)
Supervision is a series of activities ranging from planning to monitoring results to complete the follow-up to the recommendations contained in the Report of Examination (LHP), which aims to see the commitment of the leadership of the examination results and performance improvement work units (SKPD). Inspectorate is one element that has the task of internal supervision within the Ministry. Inspectorate in recording the results of monitoring internally is still done manually, from the issuance of task orders, recording examination report (LHP) and the follow-up examination (TLHP) is often contained errors and were often late, so the inspector trouble to report the findings of disciplinary violations performed by employees each SKPD. To overcome the delays and errors LHP and TLHP would require an information system monitoring using methods Design System Research Method (DSRM), which consists of six (6) steps, namely the identification of problems, setting goals, designing architecture in client server and system design using UML , case studies, evaluation and communication. With this system is expected to help finance a part in issuing the warrant task quickly, and the administration can make the results of the examination report (LHP) in accordance with the code of the findings and recommendations of code that has been assigned the CPC to be followed up by the Inspector.